Biopharmaceutical patent protection vs. generic drug competition: Traversing the public policy tightrope. (February 2022) - Hemphill, Thomas A.
Abstract: The Support Technology & Research for Our Nation's Growth and Economic Resilience (STRONGER) Patents Act, introduced in the 115th Congress, focuses on inter partes review (IPR) and post-grant review (PGR) proceedings that challenge patent validity at the U.S. Patent and Trademark Office, Patent Trial and Appeals Board (PTAB). Quinn, Brachmann, Malone, and Morinville (2018) evaluated patent data for the PTAB covering the first five plus years (through 2017) of the PTAB's operations, and calculate an 82.5% defect rate, i.e., where at least one patent claim is determined invalid and thus the invention not patentable. This finding could signal serious problems either with patent examination quality at the USPTO or with an aggressive PTAB. For recommended future research, further analysis of more recent (2018–21) patent-related validity data should be undertaken, as well as investigating the impact of the recently enacted CREATES Act on the relative strength of biopharmaceutical patent protection.